Faktor – Faktor yang Mempengaruhi Permintaan Sayuran Daun Oleh Rumah Makan di Kecamatan Kota Kefamenanu Kabupaten Timor Tengah Utara - I Komang Adi Wirawan; Agustinus Nubatonis (Fakultas Pertanian, Universitas Timor, 2019)
This study aims to: (i) find out the description of demand for leaf vegetables by restaurants in Kefamenanu City District, Timor Tengah Utara Regency, (ii) to find out factors that greatly affected the demand for leaf vegetables by restaurants in Kefamenanu City District, Timor Tengah Utara Regency. The study was conducted from January to September 2017. Determination of the study area was determined purposive. The sampling method was done by incidental sampling method, where the meaning of sampling was based on the thought that, the entire population unit the same opportunity to be sample. The results showed that the factors that affected the demand for vegetables (cassava, mustard, celery) were expenditures on vegetables purchases while the other independent variables in this study had no significant effected on the demand for leafes vegetables by the restaurant.